The differences of kinematic parameters long jump between finalists world championship in athletics (Berlin, 2009 - Daegu, 2011) - Pavlovic, R.; Idrizovic, K.; Kinov, S.; Joksimovic, M. (Slovak Journal of Sport Science, 2016)
In order to have successful technical analysis athletics uses modern biomechanical methods, and the obtained results are subjected to numerous analyzes. On the basis of the results of biomechanical parameters the most successful motor structure techniques of a competitor can be planned, programmed and analyzed, and based on this information projections for the top model in a given discipline can be made. Also based on these data possible gender differences between the jumpers can be analyzed, in order to possibly establish model and numerical values for both male and female population of jumpers. The survey was conducted on a sample of male and female finalists of the World Athletics Championships in Berlin 2009 and Daegu, 2011 with the aim of determining the difference between male and female in the kinematic parameters that are important in achieving the long jump score success. The sample included 32 athletes (16 male and 16 female), who participated in the finals World Championship. Using T-test module were obtained the results which established statistically significant differences between male athletes in four (44%) of the analyzed kinematic parameters. The differences were identified in the following kinematic parameters: the speed of the second step (VLCT 2SB, T=6,133) to the level of significance (p<0,001). Also were identified differences in the parameters of the length of the third step (LNGT 3SB, T=2,390), vertical speed of the rebound (VoVLCT, T=2,904) and angle take-off (ANGLE, T=-2,729) to the level of significance (p<0,05). In female differences were identified in the speed of the second step (VLCT 2SB, T=2,363) to the level of significance (p<0,05).